Precognition with and without succeeding stimulation in planarians - Alvarez, Fernando (Journal of Scientific Exploration, 2018)
To accomplish a simple technique to study precognition in the black planarian Girardia dorotocephala, and taking advantage of its strong photophobic response, an experiment was performed where 25 subjects were allowed to crawl in a 10 cm horizontal trough with one LED at each end. Two kinds of trials were carried out: during the experimental trials, and after a 5-min accustoming period, one of the two LEDs would be selected by a true random event generator REG and the experimenter would light it up for other 5 minutes. After one week the same subjects were submitted to the control trials, when exactly the same procedure was followed, although in this case the two LEDs were disconnected from the electric source. Subjects were filmed and their distance towards both LEDs was recorded at the very moment of stimulation or sham stimulation, and in the 1-min period preceding stimulation or sham stimulation, the number of 5-sec periods spent locomoting away from the LED to be lit or sham lit was also recorded. The results showed that during the experimental triaIs, at the very moment of stimulation, the planarians were significantly more distant to the lit LED than to the unlit one. Unexpectedly, during the control trials the subjects were more significantly distant to the sham lit LED than to the other LED. The number of 5-sec periods spent moving away from the lit LED was also higher than that toward the unlit one, the effect being even stronger than during the experimental trials. In both kinds of trials the number of such periods significantly increased as time passed. In conclusion, distance measures provide a reliable technique for studying precognition in planarians, which appear not only able to predict impending stimulation, being also aware of it without real stimulation.